2008
DOI: 10.1165/rcmb.2007-0121oc
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic Anhydrase II and Alveolar Fluid Reabsorption during Hypercapnia

Abstract: IllinoisCarbonic anhydrase II (CAII) plays an important role in carbon dioxide metabolism and intracellular pH regulation. In this study, we provide evidence that CAII is expressed in both type I (AECI) and type II (AECII) alveolar epithelial cells by RT-PCR and Western blotting in freshly isolated rat cells. These results were further confirmed by double immunostaining with CAII antibodies and AECI-or AECII-specific markers in freshly isolated alveolar epithelial cells and rat lung tissues. Inhibition of CAII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 35 publications
1
38
0
Order By: Relevance
“…CO 2 -induced Na,K-ATPase endocytosis is mediated by AMPK. We have recently observed that hypercapnia leads to AFR impairment and promotes Na,K-ATPase endocytosis from the plasma membrane to the intracellular compartments in AECs (21,23). To determine whether activation of AMPK was required for the hypercapniainduced Na,K-ATPase endocytosis, we assessed plasma membrane Na,K-ATPase protein abundance in ATII cells exposed to high CO 2 in the presence of the AMPK inhibitor compound C. Exposure of cells to 120 mmHg CO 2 decreased the plasma membrane Na,K-ATPase α 1 protein abundance by approximately 45% without affecting the total Na,K-ATPase cell pools.…”
Section: High Co 2 Levels Activate Ampk In Aecsmentioning
confidence: 99%
“…CO 2 -induced Na,K-ATPase endocytosis is mediated by AMPK. We have recently observed that hypercapnia leads to AFR impairment and promotes Na,K-ATPase endocytosis from the plasma membrane to the intracellular compartments in AECs (21,23). To determine whether activation of AMPK was required for the hypercapniainduced Na,K-ATPase endocytosis, we assessed plasma membrane Na,K-ATPase protein abundance in ATII cells exposed to high CO 2 in the presence of the AMPK inhibitor compound C. Exposure of cells to 120 mmHg CO 2 decreased the plasma membrane Na,K-ATPase α 1 protein abundance by approximately 45% without affecting the total Na,K-ATPase cell pools.…”
Section: High Co 2 Levels Activate Ampk In Aecsmentioning
confidence: 99%
“…29,30 These effects of hypercapnia on the alveolar epithelia are not due to hypoxia and can be reversed by the treatment of rats with beta-adrenergic agonists. 31 Significant progress has been made in understanding the mechanisms by which high CO 2 levels lead to impaired alveolar fluid reabsorption (Fig. 1).…”
Section: Pathophysiological Effects and Molecular Responses To Hypercmentioning
confidence: 99%
“…, Motoharu OISHI 1) , Tomoko AMASAKI 4) , Satoshi SOETA 5) , Nobutsune ICHIHARA 1) , Toshiho NISHITA 2) , Masaru MURAKAMI 3) , Hajime AMASAKI 5) and Masao ASARI 1) * 1) Departments of Anatomy, 2) Carbonic anhydrase (CA; EC4.2.1.1) is a zinc-containing metalloenzyme that has many functions, including macromolecule stabilization, gas exchange, acid-base balance, ion transport, and bone resorption [17]. About 14 CA isoenzymes are widely distributed in almost all mammalian species [4].…”
mentioning
confidence: 98%
“…The immunohistochemical distribution of CA-II has been determined in the respiratory system of humans [15] and rats [2], while that of CA-VI has been reported for mice [7] and rats [8]. Recently, canine CA-VI was detected in the upper respiratory tract, in particular, in the nasal cavity [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation